A qualitative approach for a situation analysis of AMR risks in the food animal production sector - Caipo, Marisa; Gatica, María de los Ángeles; Rojas, Hernan; del Barrio, Leopoldo (Frontiers in Veterinary Science, 2023)
In response to the need to manage antimicrobial resistance (AMR), countries have produced National Action Plans (NAPs), which require detailed information of the AMR situation in all sectors. Considering the limited information that is publicly available for an analysis of the AMR situation in animal production, the FAO Regional Office for Latin America and the Caribbean (FAO RLC) developed the “FAO tool for a situation analysis of AMR risks in the food and agriculture sectors”. The objective of this paper is to present the methodology developed for a qualitative evaluation of the risk factors of AMR for animal and human health, based on terrestrial and aquatic production systems and their associated national public and private mitigation measures. The tool was developed reflecting the AMR epidemiological model and the guidelines to conduct a risk analysis of AMR from the Codex Alimentarius and WOAH. Applied in four stages of progressive development, the objective of the tool is to provide a qualitative and systematic assessment of the risks of AMR from animal production systems, for animal and human health, and to identify gaps in cross cutting factors in AMR management. The tool consists of three instruments: i) a survey to collect data for a situation analysis of AMR risks; ii) a methodological procedure for the analysis of the information obtained; iii) instructions for the preparation of a national roadmap for the containment of AMR at a national level. Based on the results from the information analysis, a roadmap is prepared by guiding and prioritizing the needs and sectoral actions for the containment of AMR under an intersectoral, multidisciplinary and collaborative approach, and according to country priorities and resources. The tool helps to determine, visualize and prioritize the risk factors and challenges that contribute to AMR from the animal production sector and that need to be addressed to manage AMR.